Implementasi Metode Optical Flow untuk Pemilihan Menu Display pada Rancang Bangun Sistem Deteksi Pergerakan Kepala - Nyoman Kresna Aditya Wiraatmaja; Fitri Utaminingrum (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The Ministry of Health has collected data on persons with disabilities for 2018 which through Riskesdas in 2018 obtained 3 categories for persons with disabilities. First, there are people with disabilities aged 5-17 years who have disabilities reaching 3.3% throughout Indonesia. The second category is adults with disabilities whose age range is from 18 - 59 years which 22% experience disability in all of Indonesia. The last category is the elderly category, where people with disabilities are someone who is over 60 years old, it is stated that 22% of the elderly experience mild obstacles to carrying out their activities, 1.1% have moderate barriers, 1% have severe barriers, and 1.6% elderly are totally dependent. In this case, it is very difficult for people with disabilities to carry out normal activities or need assistance to operate electronic devices. So this study aims to create a head movement detection system with the optical flow method for selecting the navigation menu screen so that it can be used by people with hand disabilities without making direct contact. This system works by detecting the movement of the user's head, namely with broken movements to the left, right, head movements up, down, and head movements to the right. The output of the system is that the user can select the available navigation menus without making direct contact with the system. Based on the tests, the system obtained an accuracy of 94.6% and a computation time of 2.43104s in dim lighting. While in bright lighting the system gets an accuracy of 98.6% and the computation time is 2.41244s.